Measles (lecture, continuing). - Shostakovych-Koretsraya, L. R.; Mavrutenkov, V. V.; Cherhinets, A. V.; Budayeva, I. V.; Yakunina, О. M.; Chykarenko, Z. A. (Medicni Perspektivi, 2013)
The second part of the article discusses differential diagnosis during different measles periods. Routine and confirmatory laboratory diagnosis, including cytological, serological and molecular genetic methods is outlined. Criteria of suspected, probable and proved diagnosis of measles cases are provided. Principles of diagnosis formulation according to WHO criteria are described. Complications of measles according to cause (viral and bacterial), by different systems and particularities in high risk patients are considered. Complications of measles from central nervous system are described in details. Therapeutic management of measles is described in details, including indications for hospital admission, etiotropic therapy, strict indications for steroids and immunoglobulins prescription, vitamin A in dosages, therapy of complications, indications for antibiotics usage and other pathogenetic therapy. Specific therapy of measles complications from central nervous system is outlined. Active and passive immunization, anti-epidemic activities, patient follow-up after episode of measles and disease prognosis are described. The literature reference list consists of 121 items, including Cyrillic, Latin articles and electronic resources.